SOXC and MiR17‐92 gene expression profiling defines two subgroups with different clinical outcome in mantle cell lymphoma. Issue 6 (5th April 2016) - Roisman, Alejandro; Huamán Garaicoa, Fuad; Metrebian, Fernanda; Narbaitz, Marina; Kohan, Dana; García Rivello, Hernán; Fernandez, Isolda; Pavlovsky, Astrid; Pavlovsky, Miguel; Hernández, Luis; Slavutsky, Irma
Abstract : Mantle cell lymphoma (MCL) is a heterogeneous B‐cell lymphoid malignancy where most patients follow an aggressive clinical course whereas others are associated with an indolent performance. SOX4, SOX11, and SOX12 belong to SOXC family of transcription factors involved in embryonic neurogenesis and tissue remodeling. Among them, SOX11 has been found aberrantly expressed in most aggressive MCL patients, being considered a reliable biomarker in the pathology. Several studies have revealed that microRNAs (miRs) from the miR‐17‐92 cluster are among the most deregulated miRNAs in human cancers, still little is known about this cluster in MCL. In this study we screened the transcriptional profiles of 70 MCL patients for SOXC cluster and miR17, miR18a, miR19b and miR92a, from the miR‐17‐92 cluster. Gene expression analysis showed higher SOX11 and SOX12 levels compared to SOX4 ( P ≤ 0.0026). Moreover we found a negative correlation between the expression of SOX11 and SOX4 ( P < 0.0001). miR17‐92 cluster analysis showed that miR19b and miR92a exhibited higher levels than miR17 and miR18a ( P < 0.0001). Unsupervised hierarchical clustering revealed two subgroups with significant differences in relation to aggressive MCL features, such as blastoid morphological variant ( P = 0.0412), nodal presentation ( P = 0.0492), CD5 + ( P = 0.0004) and shorter overall survival ( P < 0.0001). Together, our findings show for the first time an association between the differential expression profiles of SOXC and miR17‐92 clusters in MCL and also relate them to different clinical subtypes of the disease adding new biological information that may contribute to a better understanding of this pathology. © 2016 Wiley Periodicals, Inc.